End-stage renal failure is associated with impaired coronary microvascular function. Issue 7 (November 2019) - Nelson, Adam J.; Dundon, Benjamin K.; Worthley, Stephen G.; Richardson, James D.; Puri, Rishi; Wong, Dennis T.L.; Coates, Patrick T.; Faull, Randall J.; Worthley, Matthew I.
Abstract : Background: Cardiovascular disease is the leading cause of death in patients with chronic kidney disease. Studies investigating the disproportionate burden of cardiovascular disease have occurred predominantly in the peripheral vasculature, often used noninvasive imaging modalities, and infrequently recruited patients receiving dialysis. This study sought to evaluate invasive coronary dynamic vascular function in patients with end-stage renal failure (ESRF). Patients and methods: Patients referred for invasive coronary angiography prior to renal transplantation were invited to participate. Control patients were recruited in parallel. Baseline characteristics were obtained. Coronary diameter (via quantitative coronary angiography) and coronary blood flow (via Doppler Flowire) were measured; macrovascular endothelial-dependent and independent effects were evaluated in response to intracoronary acetylcholine infusion (10 −7 and 10 −6 mol/l) and intracoronary glyceryl trinitrate, respectively. Microvascular function was evaluated by response to adenosine and expressed as coronary flow velocity reserve. Mean values were compared. Results: Thirty patients were evaluated: 15 patients with ESRF (mean age 52.1 ± 9, male 73%) and 15 control patients (mean age 53.3 ± 13, male 60%). Comorbidity profile, aside from ESRF, was well matched. Baseline coronary blood flow was similar between groups (101.6 ± 10.3 vs. 103.4 ± 9.1 ml/min, P = 0.71), as was endothelial-dependent response to acetylcholine (159.1 ± 16.9 vs. 171.1 ± 16.8 ml/min, P = 0.41). Endothelial-independent response to glyceryl trinitrate was no different between groups (14.3 ± 3.1 vs. 13.1 ± 2.3%, P = 0.73. A significantly reduced coronary flow velocity reserve was observed in the ESRF cohort compared to controls (2.34 ± 0.4 vs. 3.05 ± 0.3, P = 0.003). Conclusion: Patients with ESRF had preserved endothelial-dependent function however compared to controls, demonstrated significantly attenuated microvascular reserve. An impaired response to adenosine may not only represent a component of the pathophysiological milieu in patients with ESRF but may also provide a basis for the suboptimal diagnostic performance of vasodilatory stress in this population.